From Grafts to Human Bioengineered Vascularized Skin Substitutes - Oualla-Bachiri, Wasima (Int J Mol Sci, 2020)
The skin plays an important role in the maintenance of the human’s body physiological homeostasis. It acts as a coverage that protects against infective microorganism or biomechanical impacts. Skin is also implied in thermal regulation and fluid balance. However, skin can suffer several damages that impede normal wound-healing responses and lead to chronic wounds. Since the use of autografts, allografts, and xenografts present source limitations and intense rejection associated problems, bioengineered artificial skin substitutes (BASS) have emerged as a promising solution to address these problems. Despite this, currently available skin substitutes have many drawbacks, and an ideal skin substitute has not been developed yet. The advances that have been produced on tissue engineering techniques have enabled improving and developing new arising skin substitutes. The aim of this review is to outline these advances, including commercially available skin substitutes, to finally focus on future tissue engineering perspectives leading to the creation of autologous prevascularized skin equivalents with a hypodermal-like layer to achieve an exemplary skin substitute that fulfills all the biological characteristics of native skin and contributes to wound healing.